Dynamics and Effectiveness of SHGs in Chhattisgarh - Sahu, Banshi Lal; Ghosh, Souvik (Indian Journal of Extension Education, 2016)
The present study was conducted in randomly selected Kanker district of Chhattisgarh. A random sample of total 12  SHGs, three SHGs from each of four schemes viz. NABARD's SHG-Bank Linkage Programme (SBLP), National Rural  Livelihood Mission (NRLM), Integrated Watershed Management Programme (IWMP), Agricultural Technology  Management Agency (ATMA), were selected. From each of 12 SHGs a sample of 10 members were chosen as  respondents in present study. The overall dynamics of SHGs studied based on 10 different indicators showed that fund  generation, participation and norms were three most effective indicators while decision making, membership feeling and  group atmosphere were relatively less effective. Overall, the dynamics of SHGs was not much varied (overall score  ranged from 72.90 to 75.43). SHGs under ATMA showed relatively lesser values for most of the indicators resulting  relatively low dynamics as compared to the SHGs under NABARD's SBLP, NRLM and IWMP. There were no significant  differences between perceptions of members of SHGs formed under four different programmes with respect to self-help  group dynamics as evident from t-tests. Chi-square (x ) test of independence also showed the dynamics of SHGs  perceived by the members was independent of their SHGs formed under different programmes. Age, caste, economic  status and family land holding were significantly and negatively correlated with dynamics of SHGs. On the other hand,  use of personal localite communication sources, use of mass media sources, communication/ information use pattern and  satisfaction of SHG member being part of her/ his SHG were significantly and positively correlated with dynamics of  SHGs. In the step-wise regression analyses, eight variables pertaining to characteristics of SHG members viz. use of  personal localite communication source, economic status, age, sex, satisfaction of member being part of her/ his SHG, use  of mass media communication source, caste, and family land holding, together explained about 73 per cent variations  (R2= 0.728) in dynamics of SHG.
Keywords: Group dynamics; group effectiveness; SHG members